Elimination of E. faecalis and C. albicans Biofilm: A Comparison Between Single and Multiple File Systems in an Ex Vivo Study - Verónica Méndez-González (Odovtos - International Journal of Dental Sciences, 2023)
To evaluate whether the WaveOne Gold and Reciproc single file instrumentation systems, are effective in reducing the microbial load of a mixed biofilm and the cleaning of apical third compared to the Twisted File Adaptive system (multiple- file system). Seventy mesial roots of the first and second molars were included and randomly divided into three experimental groups (n=20, n=10 controls). Biofilms were formed inside canals over 31 days. After instrumentation with the unique file systems, WaveOne Gold and Reciproc and the multiple file system Twisted File Adaptive, using 2.25% sodium hypochlorite as an irrigant in all cases, a count of colony forming units was performed using serial dilutions, cleaning of the apical third was evaluated using scanning electron microscopy. Comparisons amongst groups were made by using parametric and non-parametric statistics, according to a normal or non-normal data distribution, respectively. No significant differences in the reduction of the microbial load after employing a single-file system in comparison to the multiple-file system were found; in addition, the cleaning of the apical third was similar for the three different instrumentation systems. The single-file system is equal in effectiveness compared with the multiple-file system in reducing the microbial load.